IMPACT OF THE PERIOPERATIVE NURSE ON SURGICAL PATIENT SAFETY: PRACTICES TO PREVENT INADVERTENT RETENTION OF QUANTIFIABLE ITEMS - Reis, Carla; Pereira, Cátia; Cortez, Carolina; Ferreira, Andreia; C R Henriques, Inês (Health and Society, 2023)
Background: The inadvertent retention of quantifiable items (RIIQ) continues to be an occurrence in surgical realities, which entails catastrophic consequences for the patient. IIRQ prevention translates into a collective effort where all members of the surgical team must take responsibility and adopt preventive strategies. Objective: To determine what promotes surgical count (SC) practices that ensure surgical patient safety. Methodology: The literature search was carried out in the CINAHL and Pubmed databases. It included all studies published in English or Portuguese from 2016 to 2020. Results: 6 articles were obtained. Most episodes of IIRQ occur in general surgery surgeries and where CC has been performed. The achievement of the reported CC is 77.4% and 86.5%. There is a statistically significant correlation between instrumentalist nurses and CC. Factors such as emergent, long-term surgeries, inexperienced nurses, complacency in surgical counts, different surgical teams for the same procedure, and communication failures contribute to IIRQ. There is a relationship between body mass index (BMI) and the occurrence of IIIQ. Discussion: IIIQ is a sentinel event that has a direct negative impact on patient safety and health. The risk of IIIQ is not unique to abdominal surgery, and minimally invasive surgery is not risk-free. IIRQ occurs due to several factors, although CC alone does not prevent IIRQ, it is necessary to keep in mind that it is a surgical error and, like all errors, it is preventable. Conclusion: The correct practice of CC by perioperative nurses should be a priority in all surgical interventions. This practice contributes to the prevention of IIRQ, increasing the safety of the surgical patient.